2014
DOI: 10.1016/j.livsci.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum anoestrus in tropical beef cattle: A systems approach combining gene expression and genome-wide association results

Abstract: The length of the post-partum anoestrous interval affects reproductive efficiency in many tropical beef cattle herds. In this study, results from genome-wide association studies (Experiment 1: GWAS) and gene expression (Experiment 2: microarray) were combined in a systems approach to reveal genetic markers, genes and pathways underlying the physiology of post-partum anoestrus in tropically adapted cattle. The microarray study measured the expression of 13,964 genes in the hypothalamus of Brahman cows. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Some of the regions identified here have also been detected in other studies investigating reproductive traits in cattle, such as regions Chr05/8.89–10.12Mb [ 45 47 ], Chr07/3.12–3.85Mb and Chr07/41.29–42.03Mb [ 46 ], and Chr21/0.01–3.02Mb [ 46 , 47 ]. Taken together, these findings demonstrate that cattle breeds share regions that exert a great influence on reproductive traits.…”
Section: Resultssupporting
confidence: 73%
“…Some of the regions identified here have also been detected in other studies investigating reproductive traits in cattle, such as regions Chr05/8.89–10.12Mb [ 45 47 ], Chr07/3.12–3.85Mb and Chr07/41.29–42.03Mb [ 46 ], and Chr21/0.01–3.02Mb [ 46 , 47 ]. Taken together, these findings demonstrate that cattle breeds share regions that exert a great influence on reproductive traits.…”
Section: Resultssupporting
confidence: 73%
“…Using part of the data from the study of Hawken et al (2012), Fortes et al (2012) identified SNPs and chromosome regions that are directly associated with age at puberty of females and scrotal circumference in bulls. There have been some studies related to reproductive traits in zebu cattle such as: genome-wide association studies using 777k SNP panels (Irano et al, 2016;Nascimento et al, 2015;Costa et al, 2015), candidate gene/SNP studies (Fortes et al, 2013a,b), and combinations of methodologies (SNP association and gene expression; Fortes et al, 2014). The use of these technologies is being developed especially in tropical regions due to the importance of female performance in beef production profitability.…”
Section: Introductionmentioning
confidence: 99%
“…In breeding programs, causal mutations might be important and could aid genomic selection and genetic gain . According to Fortes et al (2014), causal mutations have an advantage in comparison to random SNP: they are not dependent on LD, and so they can be used for selection over generations, across breeds, and in breeds that were not in the reference population.…”
Section: Principles Underlying Multi-breed Genomic Selectionmentioning
confidence: 99%